Neovascularisation associated with posterior uveitis. Issue 11 (November 1987) - Graham, E M; Stanford, M R; Shilling, J S; Sanders, M D
Abstract : Twenty-six patients (39 eyes) with retinal neovascularisation associated with ocular inflammation were identified from the retinal vasculitis clinic at St Thomas's Hospital. Eight patients had sarcoidosis, seven patients Behçet's disease, and 11 had idiopathic retinal vasculitis. Twenty-three patients had required systemic therapy to control the inflammation and 11 patients received laser photocoagulation. Fluorescein angiography showed significant capillary closure in 15 eyes and diffuse microvascular leakage in the remaining 24 eyes. All patients had posterior vitreous detachment. The visual prognosis was good despite vitreous haemorrhage being the presenting feature in 22 eyes, and the new vessels resolved in 70% of cases. However, laser treatment was followed by a significant increase in cystoid macular oedema (p less than 0.01). This retrospective study suggests that medical therapy is the first line of treatment in this group of patients. Photocoagulation should be performed when the eye is quiet and should be reserved for patients with recurrent vitreous haemorrhages and significant capillary closure.